Naumore Storage Project Should be the Last Resort of Development on the Main Course of Rapti (West), Nepal - Shrestha, Hari Man (Hydro Nepal: Journal of Water, Energy and Environment, 2016)
Water, food and energy are three essential elements of life and, therefore, they need to be made internally secured in a long lasting manner. In the case of Nepal, river waters are the basic sources of all these elements and are the only resources available indigenously in Nepal for these purposes. Rapti (West), being medium size river of rain-fed nature, the dry spell continues long from December up to the end of May; at the same time the flood waters available particularly in July, August and September create havoc by flooding in the downstream reaches. The Kapilvastu area which can be commanded by the Rapti (West) river does not have other dependable sources for fulfilling its requirements. The only way to fulfill its requirements without affecting downstream users is, thus, to capture a portion of flood water of Rapti behind a storage dam aimed at diversion to Kapilvastu for use during dry season. An appropriate site for such purpose is located at Bhalubang. Hence, this site needs to be developed first to ensure the diversion to Kapilvastu and then a much higher storage dam site at Naumore could, later at appropriate time but within 25 to 30 years after development of Bhalubang site, be developed for increasing the flow regulation potential of the Rapti River so that the hydropower generation, flood control and intensification of irrigated agriculture at its commendable areas, could be maximized. HYDRO Nepal Journal of Water Energy and Environment Volume- 18, 2016, January Page -1 to 5